Markers and mechanisms of resistance to Toceranib phosphate (Palladia®) in canine cutaneous mast cell tumor - Halsey, Charles H. C., author; Gustafson, Daniel, advisor; Thamm, Douglas, committee member; Ehrhart, EJ, committee member; Worley, Deanna, committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: drug resistance; Toceranib; mast cell tumor